Preheating Modeling of Forming Region and Design of Electrode Structure During Integral Electric Hot Incremental Forming - Zhengfang Li; Lijia Liu; Jiangpeng Song; Shuang Wu; Li Liu; Xinhao Zhai (Nanomaterials)
Recently, integral electric hot incremental forming technology has been proposed to form hard-to-form sheet metals and to eliminate some defects obtained through the local heating method via current, such as inhomogeneous temperature distribution, arc burns for the sheet and the tool, unsuitability for multistage forming, etc. However, the simulation of integral electric hot incremental forming involves coupled electro-thermal-mechanical analysis, which is difficult through existing simulation software. Meanwhile, the effect of the electrode structure on temperature distribution is not clear; therefore, a preheating flux model for Joule heat was proposed to simulate the temperature distribution of Ti-6Al-4V titanium alloy sheet in this work, which could simplify the coupled electro-thermal-mechanical analysis to the coupled thermal–mechanical simulation. Meanwhile, the effect of the electrode section and length on the temperature distribution was analyzed in detail, and then a design criterion for the electrode length was obtained during integral electric hot incremental forming.